A Code For The Valuation Of Mineral Properties And Projects In South Africa - A. S. Macfarlane (The Southern African Institute of Mining and Metallurgy, 2002)
The South African Institute of Mining and Metallurgy was approached by the Australian Institute of Mining and Metallurgy to present a paper on the current practice in terms of the valuation of mineral projects and properties, given the development of a Code for the Valuation of Mineral Properties, developed in Australia (the VALMIN Code), and a similar Code in Canada (the CIMVal Code).This paper is the result of research and investigation into the matter, in terms of the reporting of Mineral Resources and Reserves, financial reporting practice, the Listing Rules of the Johannesburg Securities Exchange, and various practices in valuation. The paper establishes that a strong linkage has already been established between the SAMREC Code for the reporting of Mineral Resources and Reserves and the Listing Rules, and that, for completeness, a Code for Valuation needs to be developed. This Code will be similar to its international counterparts, with the necessary inclusions which are relevant to South Africa, and will provide guidelines and definitions on matters such as transparency, materiality and competency in valuation. It proposes that a multi-stakeholder steering committee be established under the auspices of the SAIMM, to deliberate and design a process for establishing such a Code.